Dampak P5P2RA Terhadap Motivasi Belajar Siswa Kelas X MAN 1 Solok Plus Keterampilan - Dina Rahmadani; Fadhilla Yusri; Elfithri Rahmadia (STIKes Ibnu Sina Ajibarang, 2024)
Learning motivation is very important in the process of increasing learning achievement. Motivation to learn is one of the internal factors that makes a person enthusiastic about learning, because motivation to learn is essentially a driving force both from within and from outside the student. Therefore, the causes respond to desire, desire, enthusiasm, and joy in learning activities to achieve goals. With this P5P2RA activity, we hope that all students can make the best use of it. This activity allows students to learn outside the classroom and produce new work and ideas related to their projects, and this activity also makes students enthusiastic. You can study not only in class, but also outside class, so you can study without getting bored. You can also learn while playing, because there are activities that make you excited and motivated to learn, and there are also activities that require you to compete to complete each task. project. A student's level of learning motivation is determined by his behavior during the learning process. The aim of this research is to determine the impact of implementing the Pancasila and Rahmatan Lil Alamin Student Profile Improvement Project (P5P2RA) at MAN 1 Solok Plus Skills in Koto Baru Solok Regency, the principles of its implementation and its impact on students. is analyzing. Action. This research uses a qualitative descriptive research method.